Stratigraphic Characteristics and Sediment-Filling Process of the Early Permian Fengcheng Formation in the Northwestern Margin of the Junggar Basin, Northwest China - Zhi, Dongming; Liu, Mingxin; Chen, Xinwei; Said, Nuru; Tang, Wenbin; Hu, Chenhui; Qin, Zhijun; Zou, Hao; Gong, Deyu (Frontiers in Earth Science, 2022)
The Permian–Fengcheng Formation in the Mahu sag of the Junggar Basin is a crude oil reservoir and source rock. However, its stratigraphic characteristics, the boundary marks of the three members (lower, middle, and upper), and the sediment-filling processes are unclear. This paper presents the sedimentary systems and sediment-filling processes in an intracontinental rift basin of this area using sedimentary-faces analysis, sequence stratigraphy, well logs, and 2D seismic interpretations. The results show that the Fengcheng Formation consists of three third-order sequence stratigraphy (SQf1, SQf2, and SQf3). The lowest member of the Fengcheng Formation is composed of gray to dark–gray thin medium layers of tuff, lacustrine dolomitic mudstone, and argillaceous dolomite near the depocenter. Tuff and siltstone and a small amount of fan-delta glutenite, volcanic breccia, and basalt are near the fault zone. Thus, the logging curve is characterized by high GR value, high amplitude, wavelength growth, and medium frequency. Near the depocenter, the middle member of the Fengcheng Formation comprises gray and gray–black thin layers of lacustrine muddy dolomite and dolomitic mudstone, as well as thin sandstone and mudstone interbedded between tuff and gravel near the orogenic belt. The logging curve displays high-to-low GR values, high amplitude, short wavelength, and high frequency. The upper member of the Fengcheng Formation is not characterized by lesser tuffaceous and dolomitic components but by an increased fan-delta sandy content. The bottom of the upper member is composed of lacustrine mudstone and siltstone interbedded between dolomitic mudstones; whereas, fan-delta coarse sandstone and sandy conglomerate are common near the top of the upper member. The logging curve shows a low GR value, small amplitude, and continuous stability. The lower and middle members of the Fengcheng Formation expand during the sediment-filling process of the lake basin of the Mahu sag; whereas, the upper member contracts.